2023
DOI: 10.3389/fendo.2023.1050078
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based multimodal MRI texture analysis for assessing renal function and fibrosis in diabetic nephropathy: a retrospective study

Abstract: IntroductionDiabetic nephropathy (DN) has become a major public health burden in China. A more stable method is needed to reflect the different stages of renal function impairment. We aimed to determine the possible practicability of machine learning (ML)-based multimodal MRI texture analysis (mMRI-TA) for assessing renal function in DN.MethodsFor this retrospective study, 70 patients (between 1 January 2013 and 1 January 2020) were included and randomly assigned to the training cohort (n1 = 49) and the testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the present study, the classi cation performance seemed to be improved compared to the previous report [13], probably owing to the convolutional network we used this time, although statistical evaluation was somewhat different between the two, making precise comparison di cult. Chen et al reported excellent models classifying the renal function status in diabetic nephropathy, with coronal T2WI-based radiomics analysis and machine-learning model combined with the measured BOLD and DWI values [24]. They suggested that renal brosis causes decreased signal intensity on T2WI, thus these changes can be evaluated quantitatively [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the classi cation performance seemed to be improved compared to the previous report [13], probably owing to the convolutional network we used this time, although statistical evaluation was somewhat different between the two, making precise comparison di cult. Chen et al reported excellent models classifying the renal function status in diabetic nephropathy, with coronal T2WI-based radiomics analysis and machine-learning model combined with the measured BOLD and DWI values [24]. They suggested that renal brosis causes decreased signal intensity on T2WI, thus these changes can be evaluated quantitatively [24].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported excellent models classifying the renal function status in diabetic nephropathy, with coronal T2WI-based radiomics analysis and machine-learning model combined with the measured BOLD and DWI values [24]. They suggested that renal brosis causes decreased signal intensity on T2WI, thus these changes can be evaluated quantitatively [24]. Their models were superior to our results, though the accurate comparison was di cult due to several reasons: they focused only on diabetic nephropathy and the CKD groups they classi ed were slightly different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…RF is an idea of ensemble learning, which inputs many weak learners through random sampling of data, and it could measure the relative importance of each feature for the prediction. 14 The DT is a classification and regression model based on a tree structure, which classifies or predicts data through a series of decisions. 18 The NN is an updated technology based on models with fewer assumptions, which relies on multi-layers of representation of data with continuous transformations, and it is capable of handling more complex data.…”
Section: Methodsmentioning
confidence: 99%
“… 13 For example, the random forest (RF) model has proven useful in Alzheimer’s disease and diabetic nephropathy. 14 In addition, the logistic regression model (LR), the decision tree (DT), and the neural network (NN) have shown strong capabilities in medical data processing. 15 , 16 Previous studies have demonstrated that machine learning algorithms improve the accuracy of identifying and distinguishing UC compared to using serological markers alone.…”
Section: Introductionmentioning
confidence: 99%